Helmets Sense The Hard Knocks [News]. - Jones, W.D.
The paper presents a device installed in a football player's helmet, which measures each blow to the head and reports the force of the impact. The wireless device let coaches pull football players before they suffer brain damage.
Keywords: MEMS; Biophysical instrumentation; Brain damage; Football helmets; Head impact telemetry system; Impact force; Wireless device